2016
DOI: 10.1002/esp.3938
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of overland flow connectivity in bare agricultural plots

Abstract: Soil surface roughness not only delays overland flow generation but also strongly affects the spatial distribution and concentration of overland flow. Previous studies generally aimed at predicting the delay in overland flow generation by means of a single parameter characterizing soil roughness. However, little work has been done to find a link between soil roughness and overland flow dynamics. This is made difficult because soil roughness and hence overland flow characteristics evolve differently depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 71 publications
5
35
0
Order By: Relevance
“…Of all the small depressions on Surface 3, most were gradually filled and thus, exhibited a smooth, rather than sudden, stepwise increases in CA (Figure a). This finding is similar to those from the RSCf analyses by Antoine et al () and Peñuela et al ().…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Of all the small depressions on Surface 3, most were gradually filled and thus, exhibited a smooth, rather than sudden, stepwise increases in CA (Figure a). This finding is similar to those from the RSCf analyses by Antoine et al () and Peñuela et al ().…”
Section: Resultssupporting
confidence: 92%
“…From the D‐cubed delineation and P2P simulation, the new NACf analysis was developed. Other studies have identified and quantified contributing area by dividing it into two parts, contributing to the outlet and noncontributing area (Antoine et al, ; Peñuela et al, , ). In this study, a noncontributing area was further divided by identifying and quantifying connectivity of areas that were not connected to the outlet to investigate how these ACs changed spatially and temporally.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were dependent on the different land uses and tillage practices. This proposal agreed with observations by Peñuela et al (2016) who proposed a link between differences in soil roughness values and overland flow dynamics (diffuse or concentrated) in tilled plots monitored for two years using 0.01 m resolution DEMs. The evolution of these metrics agreed with the results of Brasington et al (2012), who found that all geospatial metrics in a long braided river reach experienced a significant loss of topographic complexity with decreasing DEM resolution (from 0.1 to 1 m).…”
Section: Discussionsupporting
confidence: 90%
“…Soil roughness characterisation in tilled soils depends on the spatial resolution of the topographic data; whereas, at the same time, soil roughness, overland flow dynamics and functional connectivity evolve differently depending on whether diffuse or concentrated runoff dominates (Peñuela et al, 2016). However, we did not find any studies that investigated the effect of DEM resolution on the magnitude and patterns of modelling HC in woody crops.…”
Section: Introductionmentioning
confidence: 59%
“…As a consequence, this approach does not reflect the effect of conservative tillage and no‐tillage practices in minimizing soil erosion by reducing the soil disturbance and allowing more surface residue (Busari et al ., ). The MMMF approach does not take into account the direction of tillage or that roughness elements created by tillage, especially when parallel to the slope, can concentrate flow in non‐permanent channels, thereby increasing the erosion and sediment transport capacity of the flow (Govers et al ., ; Kirkby et al ., ; Gómez and Nearing, ; Peñuela et al ., ).…”
Section: Model Descriptionmentioning
confidence: 99%